CLINICAL CASE OF CHROMOSOME 22Q11.2 DELETION SYNDROME (DI-GEORGIE SYNDROME) - Ирина Анатольевна Никитина; Елена Глебовна Цой; Светлана Владимировна Цигельник; Вадим Гельевич Мозес; Светлана Ивановна Елгина; Елена Владимировна Рудаева (Мать и дитя в Кузбассе, 2020)
A clinical case of orphan genetic pathology – Di Georgi syndrome in a child in the neonatal period is presented. The complexity of timely diagnosis of this complication is demonstrated.